Structural interplays in the flexible n-terminus and scaffolding domain of human membrane protein caveolin 3 - Park, Hae Jun; Jang, Jinhwa; Ryu, Kyung Suk; Lee, Jinhyuk; Lee, Sung Hee; Won, Hyung Sik; Kim, Eun Hee; Seo, Min Duk; Kim, Ji Hun (Membranes, 2021)
Caveolins are critical for the formation of caveolae, which are small invaginations of the plasma membrane involved in a variety of biological processes. Caveolin 3 (Cav3), one of three caveolin isoforms, is an integral membrane protein mainly expressed in muscle tissues. Although various human diseases associated with Cav3 have been reported, structural characterization of Cav3 in the membrane has not been investigated in enough depth to understand the structure- function relationship. Here, using solution NMR, we characterized membrane association, structural communications, and molecular dynamics of the monomeric Cav3 in detergent micelle environment, particularly focused on the whole N-terminal part that is composed of the flexible N-terminus and the scaffolding domain. The results revealed a complicated structural interplay of the individual segments composing the whole N-terminal part, including the pH-dependent helical region, signature motif-like region, signature motif, and scaffolding domain. Collectively, the present study provides novel structural insights into the whole N-terminal part of Cav3 that plays important biological roles in cellular processes and diseases. In particular, given that several disease-related mutations are located at the whole N-terminal part of Cav3, the sophisticated communications in the whole N-terminal segments are likely to have relevance to the molecular basis of Cav3-related disease.
Keywords: Biological process; Cellular process; Integral membrane proteins; Membrane association; Membrane proteins; Structural characterization; Structural insights; Structure-function relationship; Caveolin 3; Nuclear magnetic resonance; Oligomerization; Paramagnetic relaxation enhancement; Signature motif